Let $a$, $b$ and $c$ be non-negative numbers. Prove that: $$a\sqrt{a^2+bc}+b\sqrt{b^2+ac}+c\sqrt{c^2+ab}\geq\sqrt{2(a^2+b^2+c^2)(ab+ac+bc)}.$$

I have a proof, but my proof is very ugly:

it's enough to prove a polynomial inequality of degree $15$.

I am looking for an easy proof or maybe a long, but a smooth proof.

  • 2
    $\begingroup$ If you assume $abc=1$, then $a^2+bc=a+a^{-1}$ $\endgroup$ – Empy2 Jan 1 '16 at 10:58
  • $\begingroup$ What is a rest? $\endgroup$ – Michael Rozenberg Jan 1 '16 at 10:59
  • 1
    $\begingroup$ No, it was just a thought, I don't have a full proof. $\endgroup$ – Empy2 Jan 1 '16 at 11:00
  • 2
    $\begingroup$ I tried smth, but getting a contradiction from it...: Let $abc=1$. $\sqrt{x^2+\frac1x}$ is convex (see W/A) so by weighted Jensen, $LHS\geq\sqrt{\frac{\sum a(a^2+\frac1a)}{\sum a}}\cdot\sum a=\sqrt{(a+b+c)(a^3+b^3+c^3+3abc)}$, but for $a\to0$ the reverse inequality is true (by e.g. Cauchy-Schwarz), so what did I do wrong? $\endgroup$ – rabota Jan 1 '16 at 12:25
  • 2
    $\begingroup$ To barto. It's wrong because $f(x)=\sqrt x$ is a concave function. $\endgroup$ – Michael Rozenberg Jan 1 '16 at 17:48

This inequality is beautiful and tight. Equality holds when $a=b=c$, or $a=b$ and $c=0$.

Now we use the S.O.S. (sum of squares) technique to solve it (about this technique, see Sos - sum of squares for details).

First, squaring on both sides, it suffices to show

$$\sum a^2 \left( a^2+bc \right) + 2\sum bc\sqrt{\left( b^2+ca \right) \left( c^2+ab \right)} \ge 2\left( \sum a^2 \right) \left( \sum bc \right)\\ \Longleftrightarrow \sum a^4 + abc \sum a + 2\sum bc\sqrt{\left( b^2+ca \right) \left( c^2+ab \right)} \ge 2\sum bc\left( b^2+c^2 \right) + 2abc \sum a.$$

Note (from the formulation of Schur's inequality) that $$\sum \left( b^2 + c^2 - a^2 \right) (b-c)^2 = 2 \sum a^4 - 2 \sum bc\left( b^2 + c^2 \right) + 2abc\sum a.$$

Thus the inequality is equivalent to

$$\frac{1}{2} \sum \left( b^2 + c^2 - a^2 \right)(b-c)^2 + 2\sum bc \sqrt{\left( b^2+ca \right) \left( c^2+ab \right)} \ge \sum bc\left( b^2 + c^2 \right) + 2abc \sum a.$$

Note that

$$\sum bc \left( \frac{(b-c)(b+c-a)}{\sqrt{b^2+ca} + \sqrt{c^2+ab}} \right)^2 = \sum bc \left( \sqrt{b^2+ca} - \sqrt{c^2+ab} \right)^2\\ = \sum bc \left( \left( b^2+ca \right) + \left( c^2+ab \right) \right) - 2 \sum bc \sqrt{\left( b^2+ca \right) \left( c^2+ab \right)}\\ = \sum bc \left( b^2+c^2 \right) + 2abc \sum a - 2 \sum bc \sqrt{\left( b^2+ca \right) \left( c^2+ab \right)}.$$

Thus the inequality is equivalent to

$$\sum \left( b^2+c^2-a^2 - \frac{2bc(b+c-a)^2}{\left( \sqrt{b^2+ca} + \sqrt{c^2+ab} \right)^2} \right) (b-c)^2 \ge 0.$$

Note that

$$\left( \sqrt{b^2 + ca} + \sqrt{c^2 + ab} \right)^2 = b^2+ca+c^2+ab + 2\sqrt{\left( b^2+ca \right) \left( c^2+ab \right)}\\ \ge b^2+ca+c^2+ab+2bc=(b+c)(a+b+c),$$

and similarly

$$\left( \sqrt{c^2 + ab} + \sqrt{a^2 + bc} \right)^2 \ge (c+a)(a+b+c)\\ \left( \sqrt{a^2 + bc} + \sqrt{b^2 + ca} \right)^2 \ge (a+b)(a+b+c).$$

So if we define

$$S_a = b^2+c^2-a^2 - \frac{2bc(b+c-a)^2}{(b+c)(a+b+c)},\\ S_b = c^2+a^2-b^2 - \frac{2ca(c+a-b)^2}{(c+a)(a+b+c)},\\ S_c = a^2+b^2-c^2 - \frac{2ab(a+b-c)^2}{(a+b)(a+b+c)},$$

then we only need to show $\sum S_a (b-c)^2 \ge 0$. Without loss of generality, we assume that $a \ge b \ge c$. In a post by hungkhtn in Sos - sum of squares, we know that it suffices to show

$$S_b \ge 0,\ S_c\ge 0,\ a^2 S_b + b^2 S_a \ge 0.$$


$$\left( c^2+a^2-b^2 \right)-(c+a-b)^2=2b(c+a)-2ca-2b^2=-2(b-a)(b-c)\ge 0\\ \Longrightarrow \left( c^2+a^2-b^2 \right) (c+a)(a+b+c)\ge (c+a-b)^2\cdot (c+a)(a+b+c)\ge 2ca(c+a-b)^2,$$

which means $S_b\ge 0$.


$$\left( a^2+b^2-c^2 \right)(a+b)(a+b+c) - 2ab(a+b-c)^2\\ = \left(a^2+b^2\right) (a+b)^2 + \left(a^2+b^2\right)(a+b)c- (a+b)^2 c^2 - (a+b)c^3\\ - 2ab(a+b)^2 + 4abc(a+b) - 2abc^2\\ = (a-b)^2 (a+b)^2 + \left( \left(a^2+b^2\right)(a+b)c - (a+b)^2 c^2 \right) + \left( 4abc(a+b) - 2abc^2 - (a+b)c^3 \right)\\ \ge 0,$$

which means $S_c \ge 0$.


$$a^2 S_b + b^2 S_a \ge 0\\ \Longleftrightarrow a^2 c^2 + a^4 - a^2 b^2 + b^4 + b^2 c^2 - b^2 a^2 \ge \frac{2ca^3(c+a-b)^2}{(c+a)(a+b+c)} + \frac{2b^3 c(b+c-a)^2}{(b+c)(a+b+c)}\\ \Longleftrightarrow (a+b+c)\left( (a+b)^2 (a-b)^2 + \left( a^2+b^2 \right) c^2 \right) \ge \frac{2ca^3 (c+a-b)^2}{c+a} + \frac{2cb^3 (c+b-a)^2}{c+b}.$$

Note that the right hand side is not greater than

$$2ca^2 (c+a-b)^2 + 2cb^2 (c+b-a)^2\\ = \left( 2c^3 a^2 + 4c^2 a^2 (a-b) + 2ca^2 (a-b)^2 \right) + \left( 2c^3 b^2 + 4c^2 b^2 (b-a) + 2cb^2 (a-b)^2 \right)\\ = 2c^3 \left( a^2 + b^2 \right) + 4c^2 (a+b)(a-b)^2 + 2c\left( a^2 + b^2 \right)(a-b)^2\\ \le (a+b+c)\left(a^2+b^2\right)c^2 + 4c^2 (a+b)(a-b)^2 + 2c\left( a^2 + b^2 \right)(a-b)^2.$$

So it remains to show

$$(a+b+c)(a+b)^2 \ge 4c^2(a+b) + 2c\left( a^2+b^2 \right)\\ \Longleftrightarrow (a+b)^3 \ge 4c^2 (a+b) + c(a-b)^2\\ \Longleftrightarrow (a+b)\left( (a+b)^2 - 4c^2 \right) \ge c(a-b)^2,$$

which is obviously true, since $(a+b)^2 - 4c^2 \ge (a+b)^2 - 4ab = (a-b)^2$ and $a+b\ge c$.







$\Leftrightarrow\sum\limits_{cyc}(a-b)^2(a+b-c)^2\left(1-\frac{2ab}{\left(\sqrt{a^2+bc}+\sqrt{b^2+ac}\right)^2}\right)\geq0$, which is obvious.


protected by Community Feb 12 '16 at 17:31

Thank you for your interest in this question. Because it has attracted low-quality or spam answers that had to be removed, posting an answer now requires 10 reputation on this site (the association bonus does not count).

Would you like to answer one of these unanswered questions instead?

Not the answer you're looking for? Browse other questions tagged or ask your own question.